2019
DOI: 10.1016/j.brs.2018.12.224
|View full text |Cite
|
Sign up to set email alerts
|

The neuromodulatory and hormonal effects of transcutaneous vagus nerve stimulation as evidenced by salivary alpha amylase, salivary cortisol, pupil diameter, and the P3 event-related potential

Abstract: Background: Transcutaneous vagus nerve stimulation (tVNS) is a new, non-invasive technique being investigated as an intervention for a variety of clinical disorders, including epilepsy and depression. It is thought to exert its therapeutic effect by increasing central norepinephrine (NE) activity, but the evidence supporting this notion is limited. Objective: In order to test for an impact of tVNS on psychophysiological and hormonal indices of noradrenergic function, we applied tVNS in concert with assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
152
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(191 citation statements)
references
References 60 publications
(80 reference statements)
13
152
9
Order By: Relevance
“…Transcutaneous VNS is a recent development that holds promise for non-invasive and low-risk stimulation of the vagus nerve, by electrically stimulating its cervical or auricular branches, which are situated close to the surface of the skin of the neck and outer ear, respectively. However, it was recently reported that t-VNS though its auricular branch did not affect pupil size (Keute et al, 2019;Warren et al, 2019). The discrepancy between these findings and ours implies that the transcutaneous protocol likely insufficiently stimulated the vagus nerve, perhaps due to the site of stimulation (auricular vs cervical branches) or due to the chosen stimulation parameters (pulse amplitude, width, rate).…”
Section: Discussioncontrasting
confidence: 83%
“…Transcutaneous VNS is a recent development that holds promise for non-invasive and low-risk stimulation of the vagus nerve, by electrically stimulating its cervical or auricular branches, which are situated close to the surface of the skin of the neck and outer ear, respectively. However, it was recently reported that t-VNS though its auricular branch did not affect pupil size (Keute et al, 2019;Warren et al, 2019). The discrepancy between these findings and ours implies that the transcutaneous protocol likely insufficiently stimulated the vagus nerve, perhaps due to the site of stimulation (auricular vs cervical branches) or due to the chosen stimulation parameters (pulse amplitude, width, rate).…”
Section: Discussioncontrasting
confidence: 83%
“…Although the present findings are remarkably consistent with studies that related gate switching in the reference-back task to a dopaminergic marker (Rac-Lubashevsky, Slagter, & Kessler, 2017) and activity in BG (Nir-Cohen et al, 2019), an explanation of the present results in terms of noradrenaline cannot be definitively ruled out. Future research therefore should include and control for measures of noradrenaline activity, for example pupil dilation (Joshi, Li, Kalwani, & Gold, 2016;Murphy, O'Connell, O'Sullivan, Robertson, & Balsters, 2014;Reimer et al, 2016) or salivary alpha amylase levels (Warren et al, 2019;Warren, van den Brink, Nieuwenhuis, & Bosch, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Further some of these clip electrodes are made from a high impedance rubber or carbon that is not ideal for noninvasive, transcutaneous electrical nerve modulation. Other fairly coarse approaches have implemented small (1-2 mm) stainlesssteel ball electrodes positioned at two or more locations in the concha and external ear [39], which can result in discomfort due to high current densities at the electrode-skin interface.…”
Section: Human Dimensions and Real-world Considerations For Auricular Vmentioning
confidence: 99%
“…We analyzed the continuous EEG spectral data collected globally from channels F3, Fz, F4, C3, Cz, C4, P3, Pz, and P4 during passive auditory tasks before and following taVNS treatment. For each of the treatment conditions evaluated, we investigated changes in the absolute and relative power of the following EEG spectral bands: delta (1 -4 Hz), theta (4 -8 Hz), alpha (8 -12 Hz), beta 1 (12 -15 Hz), beta 2 (15)(16)(17)(18)(19)(20), beta 3 (20 -30 Hz) and gamma (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Data from these investigations are summarized in Tables 6 and 7 and illustrated in Figures 27-32.…”
Section: Influence Of Tavns On Continuous Eeg Spectral Powermentioning
confidence: 99%
See 1 more Smart Citation